Selenate tolerance and selenium hyperaccumulation in the monocot giant reed (Arundo donax), a biomass crop plant with phytoremediation potential - Domokos-Szabolcsy, Éva; Fári, Miklós; Márton, László; Czakó, Mihály; Veres, Szilvia; Elhawat, Nevien; Antal, Gabriella; El-Ramady, Hassan; Zsíros, Ottó; Garab, Győző; Alshaal, Tarek (Environmental science and pollution research international, 2018)
The response of giant reed (Arundo donax L.) to selenium (Se), added as selenate, was studied. The development, stress response, uptake, translocation, and accumulation of Se were documented in three giant reed ecotypes STM (Hungary), BL (USA), and ESP (Spain), representing different climatic zones. Plantlets regenerated from sterile tissue cultures were grown under greenhouse conditions in sand supplemented with 0, 2.5, 5, and 10 mg Se kg-1 added as sodium selenate. Total Se content was measured in different plant parts using hydride generation atomic fluorescence spectroscopy. All plants developed normally in the 0-5.0 mg Se kg-1 concentration range regardless of ecotype, but no growth occurred at 10.0 mg Se kg-1. There were no signs of chlorosis or necrosis, and the photosynthetic machinery was not affected as evidenced by no marked differences in the structure of thylakoid membranes. There was no change in the maximum quantum yield of photosystem II (Fv/Fm ratio) in the three ecotypes under Se stress, except for a significant negative effect in the ESP ecotype in the 5.0 mg Se kg-1 treatment. Glutathione peroxidase (GPx) activity increased as the Se concentration increased in the growth medium. GPx activity was higher in the shoot system than the root system in all Se treatments. All ecotypes showed great capacity of take up, translocate and accumulate selenium in their stem and leaf. Relative Se accumulation is best described as leaf ˃˃ stem ˃ root. The ESP ecotype accumulated 1783 μg g-1 in leaf, followed by BL with 1769 μg g-1, and STM with 1606 μg g-1 in the 5.0 mg Se kg-1 treatment. All ecotypes showed high values of translocation and bioaccumulation factors, particularly the ESP ecotype (10.1 and 689, respectively, at the highest tolerated Se supplementation level). Based on these findings, Arundo donax has been identified as the first monocot hyperaccumulator of selenium, because Se concentration in the leaves of all three ecotypes, and also in the stem of the ESP ecotype, is higher than 0.1% (dry weight basis) under the conditions tested. Tolerance up to 5.0 mg Se kg-1 and the Se hyperaccumulation capacity make giant reed a promising tool for Se phytoremediation.
Keywords: Poaceae; Biodegradation, Environmental; Selenic Acid; kyselina selenová; selen; biodegradace; Biomass; Spectrometry, Fluorescence; biomasa; lipnicovité; Selenium; ekotyp; Ecotype; fluorescenční spektrometrie